The practical engineer [heat sinks design]. - Soule, C.A.
Beset by time-to-market pressures, designers often neglect the thermal requirements of their products and then have to resort to costly after-the-fact fixes. From the standpoint of the system as a whole, thermal management or thermal design has to take all of the components and the operating environment as well into account. The author discusses early and effective steps to take for managing thermal design. These are: look at the system as a whole; define heat sink requirements; choosing a heat sink; selecting a thermal interface material; and computer modelling of the system
Keywords: Computer modelling; Heat sink requirements; Heat sinks design; Operating environment; Thermal design; Thermal interface material; Thermal management; Thermal requirements